P-69 Priority setting for end-of-life care. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Mellor, Peter; Grande, Gunn; Diffin, Janet; Spence, Michael; Spencer, Rebecca
Abstract : Introduction: End-of-life (EoL) care is an under-researched area. It is vital to focus on the priorities that are likely to bring the most benefit to patients, carers, and their families. This project set out to identify the EoL research priorities of healthcare professionals (HCPs) and carers in Greater Manchester. Approach: Following a scoping exercise of EOL services in Greater Manchester, comprising of semi-structured interviews with HCPs, CLAHRC GM identified six topics within the 10 national EoL research priorities outlined by PeolcPSP. The topics identified were those that we have the capability to deliver research in: Education and knowledge for staff and carers Access to 24 hour care and support Equitable Access Advance care planning Care at home Continuity of care CLAHRC GM held a priority setting event to consult with 32 HCPs and also held separate consultations with 26 carers facilitated by local carer groups from Manchester, Salford, and Bury during which HCPs and carers were asked to select their important priorities from the six topics. Outcomes: Combining carer and HCP responses, the topics of shared priority were: Advance care planning (62% carers, 56% HCPs) Access to 24-hour care (65% carers, 50% HCPs) Education and knowledge for staff and carers (73% carers, 34% HCPs) Whilst all topics were generally viewed as important by carers, there was more emphasis placed on training and education as the main priority whilst HCPs focused more on advance care planning. HCPs also identified important research questions within their chosen topics. Next steps: The shared priorities will be used to develop the research questions identified by HCPs and, through further carer input, will shape the EoL research delivered across Greater Manchester over the next few years.